Mobile phones, income diversification, and poverty reduction in rural Bangladesh - Matsuura-Kannari, Masanori; Islam, Abu Hayat Md. Saiful; Tauseef, Salauddin (Wiley, 2024)
The widespread adoption of mobile phones (MPs) presents the possibility of creating employment and self‐employment opportunities. Although several studies have documented the impact of MPs on income, the link between MP ownership and poverty reduction channeled by income diversification has not been fully explored. This paper aims to examine this relationship using nationally representative panel data and fixed effect models to account for confounding factors and unobserved heterogeneity. Results indicate that MP ownership is associated with increased income diversification, particularly through on‐farm and off‐farm self‐employment, as well as non‐earned income. This relationship is more pronounced in households with lower levels of education and deprived areas. In addition, owning a MP is also found to decrease poverty via income diversification. Therefore, policies aimed at enhancing access to mobile technologies could create a resilient income portfolio by decreasing transaction costs and improving market efficiency, ultimately mitigating poverty in rural regions.